Post quantum secure conditional privacy preserving authentication for edge based vehicular communication. Issue 11 (19th August 2021) - Dharminder, Dharminder; Kumari, Saru; Kumar, Uddeshaya
Abstract: A vehicular ad hoc network possesses highly advanced functioning in the intelligent transportation system. This system helps moving nodes equipped with advanced smart devices, to establish reliable communication with vehicles or usable roadside units (RSUs). It has been ascertained that the privacy of the user is essential in vehicular communication to share resources among both unknown vehicles and unknown RSUs. There are some privacy‐preserving authentication schemes based on number‐theoretic assumptions, but they do not support security against quantum computers due to Shor's algorithm. Moreover, these schemes have disfavor with repeated authentication of the earlier transmitted message and being unsuccessful to search messages no longer valid during batch verification. To resolve most of the existing issues, this article brings something new to an environment, that is, edge‐computing construction into the message‐verification procedure of the system. In the proposed design, a RSU can expeditiously verify messages from nearby legitimate vehicles and broadcast to all vehicles within its communication range, which leads to a reduction in redundant verification of messages. To ensure security against quantum attacks, we have introduced an advanced design based on the hardness of a short integer solution in some random lattice. This framework guarantees autonomous driving, regular vehicular traffic flow, and a process of revocation in the advanced quantum era. Abstract : The proposed system helps moving nodes equipped with advanced smart devices, to establish reliable communication with vehicles or usable roadside units. The proposed design supports post quantum secure conditional privacy‐preserving authentication. The proposed system supports both edge computing and batch‐verification.